Government as a Key Duty Bearer in Transition Reforms from Socialism to Capitalism-The Case of Albania - Ymeraj, Arlinda (European Scientific Journal, ESJ, 2018)
The paper “Government as a key duty bearer in transition reforms from socialism to capitalism – the case of Albania”, addresses the way in which the government should exercise its power to ensure that citizens have equal access to social welfare services, enjoying their rights. Albania, like other Central and Eastern European countries experienced the past socialist system, which failed. The failure of the socialist system was the failure of the state: in political, economic and social terms. As far as economic policies are concerned, all data demonstrate the collapse of socialism, because the system was based on inefficiency, which eroded growth. Regardless of the principles of communist regimes adopted in former communist countries’ Constitutions, the past system brought neither equity nor justice, and therefore instead of “social cohesion”, the contradictions among social groups and categories, deepened. After the failure of socialism, Albania embarked on the new path aimed at establishing democratic regimes through the protection of human rights and at raising the standard of living. Albania has been proactive in ratifying international conventions relating to human rights in general and to vulnerable groups. Very recently, on June 2014, the European Council granted Albania candidate status, as a recognition for the reform steps undertaken in harmonizing its domestic organic laws and legislation with international standards. As part of these twin obligations from UN intergovernmental and EU processes, Albanian governments after the 90s have been progressively taking measures vis-à-vis efficient allocation of resources and effective distribution of social welfare. Nevertheless, Albanian citizens live in a dire reality. Therefore, after 25 years of transition, one of the main goals of reforms, “Efficient allocation of resources to boost growth and effective distribution of social welfare to enhance equity”, seems not to have been achieved. Undoubtedly, this influences the controversial opinions about the government’s control vis-à-vis government’s mode of functioning, advancing arguments that examine whether it is a question of abuse or that of concentration of power.